2019
DOI: 10.1097/coc.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nomogram for Hepatitis B Virus–related Hepatocellular Carcinoma With Adjuvant Transarterial Chemoembolization After Radical Resection

Abstract: Objectives: The objective of this study was to establish a reliable and effective nomogram for predicting prognosis of hepatitis B virus (HBV)–related hepatocellular carcinoma (HCC) with postoperative adjuvant transarterial chemoembolization (TACE). Patients and Methods: A derivation cohort of 370 HCC patients treated with postoperative TACE in the Eastern Hepatobiliary Surgery Hospital from January 2009 to December 2012 were retrospectively analyzed. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Appropriately selecting patients that will most likely benefit from TACE is therefore imperative in order to optimize outcomes without exposing patients to unnecessary therapeutic interventions. A variety of prognostic tools have been developed over the years for this purpose, utilizing clinical variables (e.g., tumor number and size) [62,63], laboratory values (e.g., AFP, γ-glutamyl transferase levels) [64,65], molecular biomarkers (e.g., Ki67, microRNA-1268a, cochlin) [66][67][68], immunologic parameters (e.g., CD8+ cell infiltration and programmed death-ligand 1 expression) [69], and circulating tumor cells [70]. However, the external validation and comparison of these tools in a prospective setting remains an unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriately selecting patients that will most likely benefit from TACE is therefore imperative in order to optimize outcomes without exposing patients to unnecessary therapeutic interventions. A variety of prognostic tools have been developed over the years for this purpose, utilizing clinical variables (e.g., tumor number and size) [62,63], laboratory values (e.g., AFP, γ-glutamyl transferase levels) [64,65], molecular biomarkers (e.g., Ki67, microRNA-1268a, cochlin) [66][67][68], immunologic parameters (e.g., CD8+ cell infiltration and programmed death-ligand 1 expression) [69], and circulating tumor cells [70]. However, the external validation and comparison of these tools in a prospective setting remains an unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis and systematic review of randomized studies of the adjuvant TACE therapy suggested that patients with low-risk recurrent HCC do not seem to benefit from the adjuvant therapy[ 33 ]. However, patients with high-risk recurrence of HCC (including tumor diameter > 5 cm, combined vascular invasion, multiple tumors or satellite lesions, and the presence of residual lesions) undergo hepatic resection followed by hepatic artery intervention as adjuvant therapy based on standardized antiviral and hepatoprotective therapy, which may reduce the postoperative recurrence rate and improve DFS/RFS and OS[ 34 , 35 ]. Huang et al [ 36 ] developed a scoring system based on data from 1150 patients with HCC who underwent hepatectomy between 2002 and 2008 to test the efficacy of the TACE adjuvant therapy.…”
Section: Adjunctive Local Treatmentmentioning
confidence: 99%
“…Patients who had experienced no recurrence one month after resection and whose liver function had returned to normal underwent postoperative adjuvant TACE. The recurrence criteria are detailed in our previous study [18]. Using the Seldinger method, adjuvant TACE was conducted for the entire remnant liver of these postoperative patients, via the proper location of the femoral artery, under the guidance of hepatic and CT angiography.…”
Section: Postoperative Management and Adjuvant Tacementioning
confidence: 99%
“…Tumor differentiation was evaluated and determined according to the Edmondson-Steiner classification [21]. The definitions of microvascular invasion (MVI) and satellite lesions were as detailed in our previous studies [18,22].…”
Section: Definitionsmentioning
confidence: 99%